Deteksi penyakit TSV (Taura Syndrome Virus) secara PCR pada udang Vannamei (Litopenaeus vannamei) dengan berbagai ekstraksi, suhu dan waktu penyimpanan - O. Surfianti .; N.C. Prihartini .; M. Fathoni .; E.R. Ekoputri .; Laminem .; R. Wilis .; E. Pujiastuti .; Sokhib .; A.D.Koswara . (Hemera Zoa, 2010)
The shrimp farming industries have been adversely affected by epizootics due to viral pathogens, especially Taura Syndrome Virus (TSV). The TSV has been causative agent of economically disastrous epizootics in Panaeus vannamei, causing mass mortalities of 40%-90% in affected post larval and juvenile population. The current diagnostic and detection methods for TSV included clinical signs, gross pathology, in situ hybridization, and PCR. Three RNA extraction methods, i.e. RNA lysis buffer with Guanidine - HCL, RNA lysis buffer with beta-mercaptoethanol dan phenol-chloroform) were used the RNA lysis buffer with beta-mercaptoethanol, constantly had the highest yield as measured (quality and quantity) using a geneQuant spectrophotometer at period af 3 month in -20° C storeage, except the one extracted by phenol - chloroform extraction had the highest yield quantity at -80°C. Each of 3 (three) extraction methods yielded sufficient RNA for positive result in a RT PCR for TSV at period of 1 month, and 2 months, in both temperature storage (-20°C and -80°C), but at period of 3 months, only the phenol - chloroform extraction give positive result after it was stored at -20°C and -80°c.